Theoretical Experiments on Road Profile Data Analysis using Filter Combinations - Djoko Wahyu Karmiadji; M. Rosyidi; Tri Widodo; Harris Zaenal; Nofriyadi Nurdam; Andi M. Kadir; Sofwan Hidayat; Sahid Bismantoko; Nurhadi Pramana; Winarno Winarno (Universitas Muhammadiyah Magelang, 2023)
Identification of road profiles is needed to provide the input of automotive simulation and endurance testing. The analysis with estimation methods is mostly done to identify road profiles. The main goal of analysis methods is to obtain the data of vertical displacements due to road profile measurement. The acceleration data is obtained from measuring road profile by using 4 sensors of accelerometer placed on each car wheel. The measuring data is converted to be vertical displacement data by using a